Isolasi Fungi Endofit Daun Kopi Robusta (Coffea canephora): Isolation of Endophytic Fungus Robusta Coffee Leaf (Coffea canephora) - Nilam Ratna Rizkyanti; Herman Herman; Fika Aryati (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Endophytic fungi are organisms that live in plant tissues that have the potential to produce the same secondary metabolites as their host. This study attempted to isolate and also characterize endophytic fungi from Robusta coffee leaves (Coffea canephora). Data collection was carried out in several stages, namely isolation of endophytic fungi by surface sterilization method, and conventional characterization of endophytic fungi by observing the morphology of endophytic fungi. The results showed that as many as 4 isolates of endophytic fungi were isolated from Robusta coffee leaves (Coffea canephora) with macroscopic characteristics of white color with orange circle edges, cotton-like shape, and green and orange spots on the underside of the fungus.